The use of evidence-informed sustainability scenarios in the nursing curriculum: Development and evaluation of teaching methods - Richardson, Janet; Grose, Jane; Doman, Maggie; Kelsey, Janet (Nurse education today, 2014)
Climate change and resource scarcity pose challenges for healthcare in the future, yet there is little to raise awareness about these issues in the nursing curriculum and nurses are poorly equipped to practice in a changing climate. The aims of this paper are to describe how an evidence-informed ‘sustainability and health’ scenario based on two sustainability issues (resource depletion and waste management) was introduced into a nursing clinical skills session, and to report the evaluation of the session. Based on evidence from our own research on waste management, sustainable procurement and resource scarcity, a practical hands-on skill session was delivered to 30 second year student nurses as part of a scheduled clinical skills day. The session was observed by one of the facilitators and interactions recorded and this was followed by a brief questionnaire completed by participants. Observations of the group sessions and discussion found that students demonstrated limited knowledge about natural resources (such as oil) used in the production of items used in healthcare; they engaged in discussions following the use of Internet resources, and were able to segregate waste appropriately. Thirty (100%) students completed the evaluation questionnaire, found the resources used in the skill session helpful, and thought that the scenarios were realistic. Nineteen reported being more aware of peak oil; 30 were more aware of risks to patient experience and service delivery if resources become unavailable; 30 reported greater awareness of the management of waste in healthcare. Comments on the questionnaire indicated a high level of engagement and interest in the subject. The problem of climate change and resource scarcity can too easily be seen as a distant or intractable problem. However one way to make this topic real for students is through the use of clinically relevant scenarios in skill sessions.